Pengaruh Penyuluhan Terhadap Peningkatan Kompetensi Kader Posyandu Lansia - Roni, Iryadi; Rica Arieb, Shintami; Ade Rahayu, Prihartini (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The Elderly Posyandu is a forum for seeking the elderly as the main target and pre-elderly as the target of prevention in Indonesia so that they can live a healthy and productive old age based on community resources (UKBM), with a focus on promotive and preventive health services. The purpose of this study was to determine the effect of counseling on increasing the competence of elderly posyandu cadres in Ujungbaris village Widasari district Indramayu city. Village. This type of research is an experimental research type of pre-experimental research with the research design being One-Group Pretest-Posttest Design. The population in this study were all active elderly posyandu cadres in XXX in 2022, totaling 48 of the 5 existing elderly posyandu. In this study using total sampling. Based on the results of the t test it is known that µ after (11.229) > µ before (11.625) so it can be concluded that there is a difference in competence between before and after counseling. The t test shows the value of t = 9.765 with degrees of freedom (df) = 47 and sig 0.000 which means that Ho is rejected and Ha is accepted. So it is proven that there is a significant influence of counseling on the management of the elderly posyandu on the competence of the elderly posyandu cadres. It is important to carry out training and increase competence for elderly posyandu cadres to be able to increase their ability to carry out posyandu activities for the elderly.